2012
DOI: 10.1177/193229681200600521
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic Markers of Impaired Glucose Metabolism: Effects of Sleep-Disordered Breathing

Abstract: Abbreviations: (ANOVA) analysis of variance, (BMI) body mass index, (BRSPTT) baroreflex sensitivity determined using pulse transit time, (CFS) Cleveland Family Study, (ECG) electrocardiogram, (FBG) fasting blood glucose, (HRV) heart rate variability, (IFG) impaired fasting glucose, (IGM) impaired glucose metabolism, (IGT) impaired glucose tolerance, (mRRI) mean R-R interval, (OGTT) oral glucose tolerance test, (PLETH) photoplethysmograph, (PSG) polysomnogram, (PTT) pulse transit time, (RDI) respiratory disturb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 50 publications
1
2
0
Order By: Relevance
“…This is consistent with a previous study that subjects with impaired glucose metabolism, regardless of the presence of OSAS, had suppressed heart rate baroreflex [12]. This suggests that insulin resistance has stronger negative impact on the cardiac autonomic function thanOSAS.…”
Section: Discussionsupporting
confidence: 93%
“…This is consistent with a previous study that subjects with impaired glucose metabolism, regardless of the presence of OSAS, had suppressed heart rate baroreflex [12]. This suggests that insulin resistance has stronger negative impact on the cardiac autonomic function thanOSAS.…”
Section: Discussionsupporting
confidence: 93%
“…We identified 29 additional studies from the hand-search of reference lists of these studies, and added six more articles received by an expert (DG). Therefore, we retrieved 143 articles to conduct a full-text review, and subsequently excluded 26 studies (1540) (Appendix 2). Thus, a total of 117 articles were selected.…”
Section: Resultsmentioning
confidence: 99%
“…Using data derived from polysomnograms in a large-scale study of sleep apnea, we have found that BRS PTT is correlated with measures of impaired glucose tolerance, in subjects with or without SDB. 70 This association suggests that these low-cost, noninvasively derived autonomic indices may be useful in practice as biomarkers of abnormal glucose metabolism or autonomic dysfunction.…”
Section: Surrogate Of Continuous Blood Pressurementioning
confidence: 99%